Cardiac toxicity in patients with lung cancer receiving thoracic radiotherapy and immunotherapy - Son, Christine; Moey, Melissa Y. Y.; Walker, Paul R.; Naqash, Abdul R.; Peach, Matthew Sean; Ju, Andrew W. (Frontiers in Oncology, 2023)
Background Immune checkpoint inhibitors (ICIs) are used to treat locally-advanced and metastatic lung cancer, which can lead to severe immunogenic-related cardiotoxicities. We assessed the risk of cardiotoxicity in ICI-treated lung cancer patients with or without cardiac radiation from thoracic radiotherapy. Methods Retrospective data was collected on Stage III-IV lung cancer patients who received ICIs between 2015 and 2018. All cardiotoxicities associated with ICI were assessed in correlation with the timing of radiotherapy (RT) in relation to ICI, and the mean RT heart dose. The rate of cardiac events in relation to RT timing and heart dose was compared using multiple logistic regression including the Framingham risk score and steroid use prior to ICI therapy. Results Of 194 ICI-treated patients evaluated, 55.2% (n=107/194) patients had received thoracic RT at a median dose of 60.4 Gy (range, 15-75). Cardiotoxicities such as non-ST elevated myocardial infarction and new onset supraventricular tachycardias were observed in 13 (12.2%) of those who had thoracic RT versus 9 (10.3%) who did not (p=0.87). 38 patients who received RT concurrently with ICI did not develop any cardiotoxicity whereas 14.1% (n=22/156) of those who did not receive concurrent RT developed cardiotoxicities (univariate, p=0.030; multivariate, p=0.055). There were no significant differences in the mean heart RT dose, Framingham risk score, and steroid treatment between patients that received concurrent RT with ICI versus non-concurrent RT/ICI. Conclusion ICI-related cardiotoxicities were not significantly associated with patients who received concurrent thoracic radiotherapy in this retrospective review. Further validation of prospective studies is needed to confirm these results.